Pseudo tumor pelvic actinomycosis revealed by colonic obstruction with hydronephrosis: Can extensive surgery be avoided? A case report - Houyem Mansouri; Ines Zemni; Malek souissi; Houda Henchiri; Sabrine Boukhris; Mohamed Ali Ayadi; Leila Achouri (Women's Health, 2023)
Pelvic actinomycosis with an intrauterine device accounts for approximately 3% of all actinomycoses. It is a chronic infectious disease characterized by infiltrative, suppurative, or granulomatous inflammation, sinus fistula formation, and extensive fibrosis, and caused by filamentous, gram-positive, anaerobic bacteria called Actinomyces israelii . The slow and silent progression favors pseudo tumor pelvic extension and exposes the patient to acute life-threatening complications, namely colonic occlusion with hydronephrosis. Preoperative diagnosis is often difficult due to the absence of specific symptomatology and pathognomonic radiological signs simulating pelvic cancer. We discuss the case of a 67-year-old woman who complained of pelvic pain, constipation, and weight loss for 4 months, and who presented to the emergency department with a picture of colonic obstruction and a biological inflammatory syndrome. The computed tomography scan revealed a suspicious heterogeneous pelvic mass infiltrating the uterus with an intrauterine device, the sigmoid with extensive upstream colonic distension, and right hydronephrosis. The patient underwent emergency surgery with segmental colonic resection and temporary colostomy, followed by antibiotic therapy. The favorable clinical and radiological evolution under prolonged antibiotic therapy with the almost total disappearance of the pelvic pseudo tumor infiltration confirms the diagnosis of pelvic actinomycosis and thus makes it possible to avoid an extensive and mutilating surgery with important morbidity.